The Metal-Driven Biogeochemistry of Gaseous Compounds in the Environment - Kroneck, Peter M.H; Sosa Torres, Martha E. (Metal Ions in Life Sciences, 2014)
MILS-14 provides a most up-to-date view of the exciting biogeochemistry of gases in our environment as driven mostly by microorganisms. These employ a machinery of sophisticated metalloenzymes, where especially transition metals (such as Fe, Ni, Cu, Mo, W) play a fundamental role, that is, in the activation, transformation, and syntheses of gases like dihydrogen, methane, carbon monoxide, acetylene, and those of the biological nitrogen and sulfur cycles. The Metal-Driven Biogeochemistry of Gaseous Compounds in the Environment is a vibrant research area based mainly on structural and microbial biology, inorganic biological chemistry, and environmental biochemistry. All this is covered in an authoritative manner in 11 stimulating chapters, written by 26 internationally recognized experts, and supported by nearly 1200 references, informative tables, and about 100 illustrations (two thirds in color). MILS-14 also provides excellent information for teaching. Peter M. H. Kroneck is a bioinorganic chemist who is exploring the role of transition metals in biology, with a focus on functional and structural aspects of microbial iron, copper, and molybdenum enzymes and their impact on the biogeochemical cycles of nitrogen and sulfur.  Martha E. Sosa Torres is an inorganic chemist, with special interests in magnetic properties of newly synthesized transition metal complexes and their reactivity towards molecular oxygen, applying kinetic, electrochemical, and spectroscopic techniques.